PERAN ISTRI SEBAGAI PENUNJANG EKONOMI KELUARGA (Kajian Fikih Sosial Kiai Sahal Mahfudh pada Masyarakat Muslim di Desa Cangkringan Kabupaten Boyolali) - Erfan, Herfin Fahri; Hilmi, Moh. Abdulloh (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2024)
This article is a study on the role of wives as supporters of the family economy within the Muslim community of Cangkringan Village, Banyudono Boyolali regency Central Java. The purpose of this research is to understand the concept of the wife as a supporter of the family’s economic livelihood from a Social Fiqh perspective. The research data includes primary data obtained through interviews and observations, as well as secondary data gathered from relevant literature. The analysis results show that the wife plays a crucial role in maintaining the family’s economic balance, in accordance with the Social Fiqh principles outlined by Kiai Sahal Mahfudh. This study provides a deeper understanding of the wife’s responsibility in supporting the continuity of the family’s economic livelihood. The findings indicate that the wife’s role is not limited to managing the household, but also involves activities in earning an income to support the family’s needs. The importance of the wife’s role in supporting the family’s economic livelihood in Cangkringan Village not only provides economic benefits, but also has a positive impact on family harmony.